Sulfonic Acid Supported on Magnetic Methylene-Based Organosilica as an Efficient and Recyclable Nanocatalyst for Biodiesel Production via Esterification - Shaker, Masoumeh; Elhamifar, Dawood (Frontiers in Energy Research, 2020)
In this paper, a novel sulfonic acid containing magnetic methylene-based organosilica with core-shell structure (Fe3O4@OS-SO3H) is synthesized, characterized and its catalytic application is investigated for biodiesel production via esterification of carboxylic acids with alcohols. The Fe3O4@OS-SO3H was synthesized via co-condensation of tetraethyl orthosilicate (TEOS) and 1,2-bis(triethoxysilyl)methane (BTEM) around magnetite nanoparticles. The Fe3O4@OS-SO3H nanocatalyst was characterized by using FT-IR, PXRD, TGA, VSM, TEM and SEM techniques. The catalytic study showed that the Fe3O4@OS-SO3H nanocomposite can be used as an effective, powerful, selective and recyclable catalyst for the esterification of carboxylic acids with alcohols at 70 °C under solvent-free conditions. This nanocatalyst was recovered and reused several times without significant decrease in efficiency and stability.